Predicting index price based on the COVID-19 cases and deaths - Nur Sabrina Razali; R. Nur-Firyal (Penerbit Universiti Kebangsaan Malaysia, 2021)
COVID-19 pandemic has impacted global financial market. In this paper, we study the impact of COVID-19 pandemic on four countries indexes which are United Kingdom, United States, Japan and Malaysia to see the effect of the spread of the virus on economy. Based on descriptive analysis, most index market suffer for a short period of time after the World Health Organization (WHO) declared COVID-19 as a pandemic on 11 March 2020. However, most markets manage to get back on track after a few months. We want to see the effect of number of COVID-19 cases and deaths on the index price because we believe that they will impact the economic growth of most countries. This will indirectly impact the countries index market as most businesses could not operate in full scale. Moreover, an increase in number of cases, most countries had to implement a partial or total lockdown which then impact the economic growth. Based on our studies, we conclude that the number of COVID-19 cases and deaths did have an impact on the four countries index price. Prediction analysis shows that the time series linear model can predict index price better than ARIMA model that relies on historical data. As of right now, COVID-19 does have a huge impact on the countries financial market and economic growth.